STUDI EFEKTIVITAS PENERAPAN KEBIJAKAN PERDA KOTA TENTANG KAWASAN TANPA ROKOK (KTR) DALAM UPAYA MENURUNKAN PEROKOK AKTIF DI SUMATERA BARAT TAHUN 2013 - Nizwardi Azkha (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Area free from tobacco (AFT) policy is the onlyeffective and inexpensive way to protect the public from thedangers of second hand smoke. In West Sumatra there arethree cities that have local regulation on this, namely Padang,Panjang Padang, and Payakumbuh, but in reality the policy hasnot been able to reduce the active smokers. This study aims todetermine the effectiveness of AFT policy in reducing smokersactive beside its effectiveness to protect the public from thedangers of second hand smoker in West Sumatera.Methods: The study was conducted with the method, a mixof quantitative and qualitative research with explanatory design.Data collection was conducted in the city of Padang, PadangPanjang and Payakumbuh. Quantitative data from 100 personswere collected using a questionnaire, while the qualitativedata was collected through in-depth interviews. Informants ineach city are representatives of Department of Health,professional organizations, community leaders, smokers andfocus group discussions. Some secondary data are obtainedthrough documents review related to the implementation ofAFT. The quantitative data is analysed using univariate analysis,and the qualitative data is analysed using content analysis.Results: Based on the quantitative data it can be seen that inthree cities in West Sumatera the smoker rate are 59%. InPadang Panjang, the regulation has been proceeded succesfulydue to the commitment of the Mayor and the legislative parlementin implementing the policies that there should not be any tobaccoadvertising as well as sanctions for smokers, especially foremployees who smoke at the office or at school, according tothe law no. 8/2009; suf ficient funds are available forsocialization and supervision AFT, a total of Rp75.000.000,00collected from tobbacco fundation and Rp24.000.000,00 fromthe budget. In Payakumbuh there is also the commitment of theMayor and the support of the Health Department according tothe Regulation of Area Free tobbacco no 15/2011. Establishmentof Supervisory Team for AFT with funds allocated forsocialization and supervision, a total amount ofRp341.278.129,00. Padang has not yet applying the AFT policyin government offices and schools, only in private sector suchas bank. Tobacco advertising still exists and there is no sanctionfor smokers despite the existing Regulation No. AFF 14/2011with accompanying funds provided Rp85.000.000,00.The study shows that the majority (60%) public opinion supportthe implementation of AFT. Some (51%) of the public say thatAFT is effective enough to reduce active smoker, over half ofrespondents thought AFT should apply to a particular location.According to 59% of respondents, smoking in public placesshould be given sanction. In Padang Panjang there is amonitoring service via SMS and phone to report breach of theregulation so that the Mayor may impose sanctions. InPayakumbuh a similar system exist through reports and spotchecks. Violaters of the regulation are given sanction by themayor. In Padang city, sanctions have not been given. Thelocal government regulation in banning advertising andpromotion of cigarettes is implemented in two cities, the city ofPadang Panjang and Payakumbuh. Some factors that affectthe implementation of AFT are dependent on the commitmentand the role of District mayor, as well as the need for communityempowerment..Conclusion: It is concluded that the AFT policy without thecommitment and support of all parties to the implementation ofAFT difficult. AFT can be effective to protect the second handsmokers and it has potential to reduce active smokers.Keywords: Effective, AFT Policy, Reducing active smokers.